Identification of the CFTR c.1666A>G Mutation in Hereditary Inclusion Body Myopathy Using Next-Generation Sequencing Analysis - Lu, Yan; Da, Yu-Wei; Zhang, Yong-Biao; Li, Xin-Gang; Wang, Min; Di, Li; Pang, Mi; Lei, Lin (Frontiers in Neuroscience, 2018)
Hereditary Inclusion Body Myopathy (HIBM) is a rare autosomal dominant or recessive adult onset muscle disease which affects one to three individuals per million worldwide. This disease is autosomal dominant or recessive and occurs in adulthood. Our previous study reported a new subtype of HIBM linked to the susceptibility locus at 7q22.1-31.1. The present study is aimed to identify the candidate gene responsible for the phenotype in HIBM pedigree. After multipoint linkage analysis, we performed targeted capture sequencing on 16 members and whole-exome sequencing (WES) on 5 members. Bioinformatics filtering was performed to prioritize the candidate pathogenic gene variants, which were further genotyped by Sanger sequencing. Our results showed that the highest peak of LOD score (4.70) was on chromosome 7q22.1-31.1.We identified 2 and 22 candidates using targeted capture sequencing and WES respectively, only one of which as CFTRc.1666A>G mutation was well cosegregated with the HIBM phenotype. Using transcriptome analysis, we did not detect the differences of CFTR's mRNA expression in the proband compared with healthy members. Due to low incidence of HIBM and there is no other pedigree to assess, mutation was detected in three patients with duchenne muscular dystrophyn (DMD) and five patients with limb-girdle muscular dystrophy (LGMD). And we found that the frequency of mutation detected in DMD and LGMD patients was higher than that of being expected in normal population. We suggested that the CFTRc.1666A>G may be a candidate marker which has strong genetic linkage with the causative gene in the HIBM family.